Muestra fotográfica: “Lima geométrica, una mirada distinta de un caminante común” - Olivera Bernales, Maurizio Andre (2021)
Lima Geometrica is an architectonic photography project that presents a new order inside of a very disordered metropolis. The communicational purpose of this exhibition is to offer the observer a different vision of the city, taking architecture as the main artistic excuse to achieve it. Each of the photographs highlight geometric concepts such as symmetry, overlap, linearity, planes and space. In order to achieve this project’s objectives, photographs of contemporary buildings were taken in the districts of San Isidro, Miraflores, Barranco, Surco and La Molina. The choice of these areas was since they are the ones with the most contemporary structures in the city. In addition, to enrich the content of this document, interviews were conducted with photography specialists and teachers of architecture and communication careers.